「進路選択に対する自己効力」の育成に関する予備的研究 : ワークブックを用いた育成法について - 浦上, 昌則 (進路指導研究, 1996)
Since Taylor & Betz's (1983) work, a number of studies have explored the relationships between career decision-making self-efficacy beliefs and various indices of career development. Despite of these studies, little is known about how to increase career decision-making self-efficacy. Urakami (1996) proposed a workbook (ECS Workbook) to enhance self-efficacy expectations regarding career decision-making. The purpose of this article was to develop ECS Workbook. For developing ECS Workbook, three studies were conducted. In the study I , the effects of ECS Workbook on career self-efficacy were examined. Results indicated that ECS Workbook had a possibility to improve subjects' career decision-making self-efficacy scores. The study II aimed at making clear the relationships between vocational information and career self-efficacy. As a result, it was revealed that facilitative vocational information given by relatives and seniors was significantly and positively related to career decision-making self-efficacy. The purpose of the study III is to investigate what is expected by career decider in using workbook. Career deciders' expectations were classified into three types of information: career search skills, experience of seniors and preparation for career entry. Based on these results, four perspectives for developing ECS Workbook were proposed. (1) In the present, workbook style is more useful than computer systems. In the future, however, the latter might become more useful than the former with development of information environment. (2) Information included in ECS Workbook should be select carefully for all workbook users. (3) To facilitate using ECS Workbook, we need to consider how information should be present in it. (4) Career counselor and vocational information library must be equipped for ECS Workbook user.